(untitled) (Al-Academy, 2022)
The decorative supplements added are important factors in determining many decorative effects and how to implement them, whether in fabrics or fashion, and also work to determine the nature of perception for both the designer and the recipient and have a key role in shaping the human personality and determining his motives and emotional tendencies in the acquisition of fabrics and fashion and the vocabulary they carry A design that has certain connotations and symbols that gain its value from the effects it leaves on the physical formations of women. The problem of the research came with the following question (What are the decorative supplements and their role in the designs of fabrics and women’s fashion?) The research also dealt with three sections, the first topic included the methodological framework in posing the problem and its importance and objectives as well as On the definition of the most important terms, and the second topic included the theoretical framework, which included the following topics: First: The concept of decorative complements in design, Second: Decorative designs in fabrics and fashion. As for the third topic, it included the research procedures to reach the objectives of the research, and it relied on the analytical description method, and then the most important results and recommendations were included, and finally the most important sources and references.1. The design models relied on industrial raw materials in the first place because of their good appearance, high ironing ability, flexibility, softness, and high ability to accept dyeing and printing techniques, which helped in showing the aesthetic aspects that are consistent with the design goal and the age stage.2. The printing technology has played a clear role in highlighting the aesthetic qualities of the decorative designs through the optical values. These values have achieved the variation in the percentage of appearance and how to influence the nature of the recipient’s perception of it, which made the technology an active role in determining the nature of the decorative supplements added and the method of influencing the recipient.